Developments And Trends Of The It Industry In The Gulf Cooperation Council (gcc) Countries - Benmoussa, Mohammed (جامعة الوادي - University of Eloued, 2023)
Economic diversification has become an urgent issue in the Arab Gulf states. Most GCC countries want to create high-tech knowledge economies, but that requires skills and research centers that are still not widely available. The GCC may be able to build a competitive technology ecosystem by importing talent from other Arab and Asian countries. GCC countries in the Middle East are turning to IT spending as governments, large organizations, and small and medium enterprises (SMEs), as well as start-ups across all industries in the region, have recognized the need to shift towards investing in the IT industry sector
مقال
Keywords: Developments ; Trends ; IT industry ; Gulf Cooperation Council